Multiple dosages of superplasticizer and workability loss of mortar - ณรงค์กูล, อัครวิชญ์; กร้ำมาตร, ปิติศานต์; วิณิชย์ล้ำเลิศ, เฉลิมชัย; ตั้งเติมสิริกุล, สมนึก (Frontiers in Engineering Innovation Research, 2011)
This research is aimed to study the effect of mode of superplasticizer introduction on workability loss behavior of fresh mortar. Ordinary Portland cement type I was used as the only binder in this study. Natural sand was used as the fine aggregate. Napthelene based superplasticizer (SP) was used as the chemical admixture. The workability of mortar is the combination between deformability and viscosity. Deformability of mortar was measured by area of mortar flow spread after the mini slump cone removal, while viscosity of mortar was measured by outlet flow time through the v-funnel. Mix proportion of mortar was designed by fixing the amount of paste and aggregate (volume of paste/void content equals to 1.6), varying water to binder ratio between 0.27-0.41, and varying superplasticizer dosage between 0.5%-2.5%. The mode of SP introduction was divided into 2 patterns; one single dosage at the beginning and multiple dosages at many elapsed times. The workability loss was considered from the initial workability of mortar at the time just after mixing and that of every 30 minutes until 2 hours after mixing. The test results were compared for the effect of SP admixing patterns on workability loss of mortar. In case of single dosage, it was found that for a certain flow spread, the mortar mixture with higher SP dosage had higher viscosity and slower workability loss. In case of long elapsed time, the mortar with multiple dosages provided better workability than the mortar with a single dosage.